The role of Ag on the stress-induced ordering of oxygen in the Ti-15Zr-15Mo alloy - Torrento, J. E. [UNESP]; Correa, D. R.N.; da Silva, M. R.; Grandini, C. R. [UNESP] (Elsevier, 2021)
In this study, the effect of substitutional Ag on the stress-induced ordering of oxygen in the Ti-15Zr-15Mo (wt%) alloy was investigated by dynamic mechanical analysis. The Ti-15Zr-15Mo-xAg (x = 0, 1, and 3) samples were produced by argon arc melting, submitted to a posterior homogenization heat treatment, hot rolling, and solution heat treatment. The dynamic mechanical analysis was performed in the tensile mode, at a maximum strain amplitude of 0.02%, between 425 and 725 K, at 1 K/min, and frequencies from 10 up to 30 Hz. The results showed a broadened and asymmetric anelastic relaxation peak around 450 and 725 K in all samples, with step decay in Young's modulus typical of stress-induced ordering phenomena. The peaks shifted towards high temperature with the increase of the frequency, indicating a thermally activated process. The peak fitting stated the presence of oxygen-type processes, produced by the interaction of matrix (Ti-O) and substitutional (Zr-O) elements, and one clustering (Ti-O-O). The amount of Ag exhibited a significant effect on the Qp−1 and Tp relationship and in the diffusional parameters D0 and τ0 of the metallic matrix, which could be related to the changes in the bcc crystalline structure's atomic bonding. Thus, the results show that the interaction of interstitial oxygen in the Ti-15Zr-15Mo alloy can be tunable by the addition of Ag, which could bring novel insights about industrial applications beyond the biomedical area.
Keywords: Diffusion; Oxygen; Silver; Stress-induced ordering; Ti alloys